The pathogenic potential of commensal species of Neisseria. Issue 2 (February 1983) - Johnson, AP
Abstract : Although Neisseria species other than N gonorrhoeae and N meningitidis normally comprise part of the commensal bacterial flora of the oropharynx, they may occasionally act as opportunistic pathogens. Infections in which these organisms have been implicated include cases of endocarditis, meningitis, septicaemia, otitis, bronchopneumonia and possibly genital tract disease. In this paper, the clinical and pathological features of such infections are described, together with a discussion of factors that may contribute to their development.